Diffusion restricted lesions in the splenium of the corpus callosum - Förster, Alex; Apfaltrer, Paul; Al-Zghloul, Mansour; Wenz, Holger; Alonso, Angelika; Groden, Christoph (In vivo, 2022)
Background/Aim: Various neurological disorders are associated with lesions predominantly or exclusively affecting the splenium of the corpus callosum (CC), such as Marchiafava-Bignami syndrome (MBS), reversible splenium lesion (RSL), and ischemic stroke (IS). The spectrum of symptoms is broad and clinical presentations may be indistinguishable. Therefore, we aimed to investigate the additional value of diffusion-weighted imaging (DWI) findings of splenial lesions in patients with MBS, RSL, and IS. Patients and Methods: Overall, 23 patients (4 patients with MBS, 10 patients with RSL, and 9 patients with isolated IS in the splenium) were identified from a magnetic resonance imaging report database and analyzed with focus on lesion localization, shape, and size on DWI, as well as relative apparent diffusion coefficient (ADC). Results: A focal hyperintensity in the splenium was observed on DWI in all patients. In MBS symmetrical boomerang-shaped lesions, in RSL central oval or round lesions, and in IS eccentric irregular lesions in the splenium were found. The median lesion size in MBS [6.25 (IQR=2.04-8.62) ml] was significantly larger than that in RSL [0.38 (IQR=0.09-0.92) ml, p=0.01], and in IS [0.09 (IQR=0.05-0.94) ml; p=0.01]. Regarding relative ADC values, no significant differences between MBS [0.32 (IQR=0.19-0.62)], RSL [0.22 (IQR=0.14-0.30)], and IS [0.27 (IQR=0.20-1.19)] were found. Conclusion: Diffusion restricted lesions in the splenium of the CC are best classified by localization, shape, and size, whereas relative ADC values are of limited value for differentiation of different neurological disorders.